Skin aging and the aesthetic medicine management: what is the role of dermocosmetics? - Bartoletti, Emanuele; Bracchi, Carlotta; Lo Presti , Angela; Sansonetti, Chiara; Scharf, Camila; Fulgione, Elisabetta; Secchi, Maura (Aesthetic Medicine, 2026)
Background: Skin aging is a complex biological process influenced by intrinsic and extrinsic factors. Intrinsic aging is genetically determined and occurs naturally over time, leading to a gradual decline in the skin's structural and functional integrity. Extrinsic aging, also known as photoaging, is primarily caused by environmental factors, such as ultraviolet (UV) radiation, pollution, and lifestyle choices like smoking and diet. The combined effect of these factors results in common signs of skin aging, including wrinkles, loss of elasticity, dryness, and hyperpigmentation.Aim: To provide an overview of the molecular mechanisms underlying skin aging and highlight the role of dermocosmetics in mitigating visible signs.Methods: A narrative synthesis of published literature addressing intrinsic and extrinsic drivers of skin aging, as well as evidence-based dermocosmetic interventions.Results: To combat skin aging, dermocosmetics play a crucial role by offering products that target these visible signs. Key active ingredients in anti-aging dermocosmetics include retinoids, antioxidants, peptides, and hyaluronic acid. Retinoids, such as retinol, are vitamin A derivatives that promote cell turnover and collagen production, reducing wrinkles and improving skin texture. Antioxidants like vitamin C and E neutralize free radicals, which are responsible for oxidative stress and skin damage. Hyaluronic acid hydrates the skin, plumping it and reducing the appearance of fine lines. In addition to these ingredients, sunscreens are essential in preventing further photoaging by protecting the skin from harmful UV rays.Conclusions: Regular and combined use of dermocosmetics, together with photoprotection and healthy lifestyle choices, can effectively delay and mitigate visible signs of skin aging, supporting both skin health and quality of life.